Expression relative of RANK, RANKL and OPG gene on Rat Femoral Fracture Healing Process in Delayed Union Model after Pulsed Electromagnetic Field exposure - Luluk yunaini (Journal of Global Pharma Technology, 2019)
Pulsed electromagnetic field (PEMF) is application medical devices in healing bone fracture. Osteoblast and osteoclast cells have regulation in femoral fracture healing process. PEMF exposure has effect in cell nucleus activity. Genes that have critical role in bone remodelling are Receptor activator of nuclear factor kappa-B (RANK), receptor activator of nuclear factor kappa-B ligand (RANKL) and osteoprotegerin (OPG).This research aimed to analysis effect PEMF exposure in improve bone fracture healing process with delay union model, which its expression level in RANK, RANKL and OPG gene. Our research used experimental design. Sample for this research was callus from rat femoral fracture with delay union. qRT-PCR technique with Livak’s measurement were used to detection expression relative. Statistic analysis used two way ANOVA with a significant differences value p <0.05. The result showed that relative expression on RANK, RANKL and OPG have significance different in PEMF group and times (days) group. We found that the PEMF group can expedite the higher expression relative of RANK, RANKL and OPG than non PEMF group. The result has concluded using PEMF can improve the healing to normal union process on rat with delay union model.